2015
DOI: 10.1097/coc.0b013e3182868c66
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide for Second-line Treatment of Advanced Hepatocellular Cancer

Abstract: Lenalidomide can be administered to patients with advanced HCC and hepatic dysfunction. Promising, and in a small percentage of patients, durable activity has been demonstrated. Investigations are needed to explore the mechanism of action of lenalidomide in HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Lenalidomide was well tolerated, with rare grade 3 toxicities. The PR rate was 15%, including 2 patients with a durable response of 32 and 36 months [16]. …”
Section: Assessment Analysis and Discussionmentioning
confidence: 99%
“…Lenalidomide was well tolerated, with rare grade 3 toxicities. The PR rate was 15%, including 2 patients with a durable response of 32 and 36 months [16]. …”
Section: Assessment Analysis and Discussionmentioning
confidence: 99%
“…Lenalidomide has been evaluated in a phase II study after sorafenib failure or intolerance, with PR of 15% and 7.6 months of mOS [82]. In an orthotopic HCC model, lenalidomide plus sorafenib showed an interesting tumor growth inhibition, with a significant increase of T cytotoxic IFN-γ infiltrating tumor cells [83].…”
Section: Indirect Immunological Strategiesmentioning
confidence: 99%
“…In the present study, cisplatin significantly reduced MDA-MB-231 cell viability at an IC 50 value of 7.8 µM. On the other hand, it is controversy and debatable whether lenalidomide can be used to control solid tumors (14,16), although lenalidomide significantly inhibited growth of the chronic lymphocytic leukemia cells (19). In the present study, we further confirmed that lenalidomide alone had only a minimal effect on MDA-MB-231 cell viability, even at a very high dose of 320 µM, far beyond the clinically achievable concentration in humans (20).…”
Section: Discussionmentioning
confidence: 88%
“…In addition to the anti-angiogenic and immunomodulatory properties, lenalidomide has been shown to have cytotoxic effect in tumor cells (13). In clinical trials, lenalidomide was either used as a single agent or in combination with other chemotherapeutic drugs in many solid tumors; for example, Said et al showed that lenalidomide in combination with 5-fluorouracil, leucovorin, and oxaliplatin was able to control advanced colorectal cancer (13), while Safran et al assessed the activity and efficacy of lenalidomide on advanced hepatocellular cancer that was previously treated with sorafenib (14), where six out of 40 patients (15%) achieved a partial response, including two patients (5%) had stable disease for more than 32 months (14). These data indicate that lenalidomide could be more effective in combination with chemotherapeutic drugs, such as gemcitabine or docetaxel (12,15).…”
Section: Introductionmentioning
confidence: 99%